Tribochemistry of imidazolium and phosphonium bis(oxalato)borate ionic liquids: Understanding the differences. (March 2023) - Rohlmann, Patrick; Black, Jeffrey J.; Watanabe, Seiya; Leckner, Johan; Shimpi, Manishkumar R.; Rutland, Mark W.; Harper, Jason B.; Glavatskih, Sergei
Abstract: Lubrication properties of imidazolium and phosphonium bis(oxalato)borate ionic liquids (ILs) are compared in a reciprocating sliding contact at 80 °C and 140 °C. Both the influence of the alkyl chain length and the cation architecture on friction, wear and lubricant breakdown are investigated. Imidazolium ILs showed lower friction than phosphonium ILs though only phosphonium-based ILs reduced wear. A longer alkyl chain reduced friction only in the case of the imidazolium-based ILs. Analysis of the wear scars was consistent with chemical breakdown solely of the anion. Chemical changes in the ILs after the tribotests were more pronounced for imidazolium-based ILs, and comparison of breakdown and tribofilm formation implicated catalysis by the imidazolium center, which, in turn, had a strong dependence on the surface self-assembly. Graphical Abstract: Self-assembly of the ionic liquid lubricant results in co-localisation of the charged components, leading to catalysed breakdown in the case of the imidazolium salts and a significant improvement in lubrication. ga1 Highlights: The effects of the nature of the cation of an ionic liquid on its lubrication properties are revealed. The Lewis acidity of the imidazolium cation is responsible for the different extent of lubricant breakdown. Chemical reactivity is shown to be modulated by self-assembly at the surface. Breakdown of the anion is a prerequisite for sacrificial tribofilm formation.